The effect of fed rates and inflation on the movement of the IDX80 index on the Indonesia Stock Exchange for the period 2021–2024 - Alyssa Desviana; Suhono Suhono; Irvan Yoga Pardistya; Liya Megawati (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the influence of the Federal Funds Rate (Fed Rate) and inflation on the performance of the IDX80 Index on the Indonesia Stock Exchange during the 2021–2024 period. Employing a quantitative approach, the study utilizes monthly secondary data obtained from the Federal Reserve, Statistics Indonesia (BPS), and the Indonesia Stock Exchange (IDX). The findings indicate that the Fed Rate exerts a negative effect on the IDX80 Index, suggesting that increases in U.S. interest rates tend to weaken stock market performance by reducing capital inflows and increasing investment uncertainty. In contrast, inflation demonstrates a positive influence when maintained within a manageable range, reflecting stable economic conditions and sustained market activity. The results further reveal that the Fed Rate and inflation jointly contribute to explaining movements in the IDX80 Index, although a substantial proportion of market fluctuations remains attributable to other macroeconomic factors. These findings underscore the importance of both global monetary policy and domestic economic stability in shaping stock market dynamics in emerging economies. The study contributes to the growing literature on capital market determinants and provides insights for investors and policymakers in responding to external and domestic economic developments. Future research is encouraged to incorporate additional macroeconomic variables, such as exchange rates, domestic interest rates, and global commodity prices, to develop a more comprehensive understanding of stock market behavior. Keywords: Fed Rate; IDX80; Inflation; Stock Price